Global vaccination coverage and disease incidence in cattle, pigs, and poultry - Alec Gleason; Isabella Impalli; Justin Sheen; Aurelio Cabezas Murillo; Bryan T. Grenfell; Simon A. Levin; Thomas P. Van Boeckel; Ramanan Laxminarayan (Proceedings of the National Academy of Sciences, 2025)
Vaccination against livestock diseases is an effective method to prevent and control the spread of pathogens and reduce antimicrobial consumption and livestock production losses. Systematic data on global vaccination coverage could unlock opportunities to expand these outcomes. In this study, we estimate annual vaccination coverage and disease incidence for 104 cattle, porcine, and poultry diseases in 203 reporting countries and territories between 2005 and 2025 using data from the World Animal Health Information System, the Food and Agriculture Organization, and published literature. We provide 686,559 data points and further evaluate 11 diseases most widely targeted by vaccination programs in 2025. The vaccination coverage for global populations at risk of these diseases in 2025 is as follows: for cattle, 16.64% (95% CI: 16.63 to 16.66) against foot and mouth disease, 33.80% (33.43 to 34.38) against lumpy skin disease, 7.46% (6.71 to 8.81) against Brucella abortus , 11.57% (10.29 to 13.36) against anthrax, and 7.93% (6.27 to 14.09) against rabies. For pigs, 6.56% (6.56 to 6.57) against classical swine fever, 4.96% (3.28 to 8.76) against anthrax, and 8.08% (5.10 to 17.20) against rabies. For poultry, 17.62% (17.37 to 18.04) against Newcastle disease, 16.71% (16.42 to 19.01) against infectious bronchitis, 9.17% (8.59 to 13.67) against infectious laryngotracheitis, 15.04% (14.63 to 18.63) against infectious bursal disease, and 8.81% (7.94 to 11.97) against Marek’s disease. Expanding vaccination efforts in India and Argentina for cattle; China and Russia for pigs; and China, Brazil, and Iran for poultry may yield the greatest reductions in global livestock disease burden.